Trabalho e Economia Familiar Agrícola : Considerações sobre o processo de reconfiguração dos Comportamentos Econômicos dos Moradores da Vila Cariongo, em Santa Rita /MA - ROCHA, Fabiano e Silva (2016)
The present paper comprehends a field study of the economic life of the inhabitants of Cariongo village in Santa Rita/MA. For the undertaking of this research we made use of a method which contemplated both qualitative and quantitative data analyses in loco observation and statistics thus, allowing us to interpret that the inhabitants of that village face a situation of crisis in the production of manioc flour, precisely, for having their right to farm their lands revoked by the INCRA, which had intervened in an agrarian conflict between the inhabitants and local grileiros . Therefore, it occurred to us that the inhabitants of Cariongo are now undergoing what we identified as a process of reconfiguration of their economic behavior. The interpretations made thereof were basically conducted by the theoretical and methodological orientation of the economic sociology of Karl Polanyi and Max Weber, apart from the analytical discussion on subsistence economies highlighting the historians Fernand Braudel and Immanuel Wallerstein who defend a rather contrary perspective to that of the neoclassical economic theory in the face of the expansion of the historical capitalism world economy. Thus, the economic field is the ultimate point of the present research and practically of the entire debate, however, there is no intention of limiting the discussion to this field alone, this way, the focus on that social reality also takes into consideration its relation to both political and cultural fields (with analysis of the educational capital) precisely given that we understand the multiple dimensions of social life as undoubtedly inseparable aspects, yet it is not about harmonious relations, the social realm is one of struggle between the agents, a realm of contention between those who dominate and those who are dominated. In regard to this analysis of the political and cultural fields we made use of the theoretical propositions of Pierre Bourdieu with his notion of domination and symbolic violence as means of appropriation of both economic and cultural capital.